Shh Signaling from the Injured Lung Microenvironment Drives BMSCs Differentiation into Alveolar Type II Cells for Acute Lung Injury Treatment in Mice - Mengyu Wu; Jing Liu; Shu Zhang; Yi Jian; Ling Guo; Huacai Zhang; Junwei Mi; Guoxin Qu; Yaojun Liu; Chu Gao; Qingli Cai; Dalin Wen; et al. (Stem Cells International)
Alveolar type II (AT2) cells are key effector cells for repairing damaged lungs. Direct differentiation into AT2 cells from bone marrow mesenchymal stem cells (BMSCs) is a promising approach to treating acute lung injury (ALI). The mechanisms of BMSC differentiation into AT2 cells have not been determined. The Sonic Hedgehog (Shh) pathway is involved in regulating multiple differentiation of MSCs. However, the role of the Shh pathway in mediating the differentiation of BMSCs into AT2 cells remains to be explored. The results showed that BMSCs significantly ameliorated lung injury and improved pulmonary function in mice with ALI. These improvements were accompanied by a relatively high proportion of BMSCs differentiate into AT2 cells and an increase in the total number of AT2 cells in the lungs. Lung tissue extracts from mice with ALI (ALITEs) were used to mimic the injured lung microenvironment. The addition of ALITEs significantly improved the differentiation efficiency of BMSCs into AT2 cells along with activation of the Shh pathway. The inhibition of the Shh pathway not only reduced the differentiation rate of BMSCs but also failed to mitigate lung injury and regenerate AT2 cells. The results confirmed that promoting AT2 cell regeneration through the differentiation of BMSCs into AT2 cells is one of the important therapeutic mechanisms for the treatment of ALI with BMSCs. This differentiation process is highly dependent on Shh pathway activation in BMSCs in the injured lung microenvironment.